2015
DOI: 10.7575/aiac.ijels.v.3n.4p.24
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ Construction on the Quality of Pre-primary Education in Tanzania

Abstract: This study explored the stakeholders' construction of quality of Pre-primary Education (PPE) based on the various dimensions of PPE in Tanzania with special attention being paid to policy as discourse. The study involved a total of 129 informants sampled differently. The study sampled parents through convenience sampling technique, while teachers and experts were sampled through maximum variation technique. The study used descriptive cross-sectional design underpinned by interpretive paradigm. It generated dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Children's ability to read and write was also found as the main outcome of a quality pre-primary education program by parents in the study conducted by Al-Shatti (2011) in Kuwait. Tandika (2015) emphasized that the mastery of literacy skills (reading, writing and counting) is crucial to children, because they increase their confidence and positive attitudes. Parents in Tandika's study stressed that they had enrolled their children in pre-primary education expecting that they would be equipped with the basic knowledge and skills for socialise with the school environment, acquire foundational knowledge and skills for smooth transition to primary school, and fulfil a prerequisite for enrolling children in primary schooling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children's ability to read and write was also found as the main outcome of a quality pre-primary education program by parents in the study conducted by Al-Shatti (2011) in Kuwait. Tandika (2015) emphasized that the mastery of literacy skills (reading, writing and counting) is crucial to children, because they increase their confidence and positive attitudes. Parents in Tandika's study stressed that they had enrolled their children in pre-primary education expecting that they would be equipped with the basic knowledge and skills for socialise with the school environment, acquire foundational knowledge and skills for smooth transition to primary school, and fulfil a prerequisite for enrolling children in primary schooling.…”
Section: Discussionmentioning
confidence: 99%
“…Parents have different reasons for sending their children to pre-primary schools ranging from social to academic skills. The reasons include acquisition of 3Rs (reading, writing and counting skills), language and independent skills, play, exploration, arts, socialization, cleanliness and respect (Gertler et al 2014;Tandika 2015;Al-Shatti 2011). Additionally, Şahin, Sak, and Şahin (2013) found that most parents expected pre-primary schools to support social skills' development of their children, express self effectively, develop self-confidence, establish effective communication and physical skills.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation